2012
DOI: 10.1111/j.1365-2249.2012.04606.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective localization of T helper subsets in labial salivary glands from primary Sjögren's syndrome patients

Abstract: The aim of this study was to investigate the initiation and progression of autoimmune damage in the lesions of labial salivary glands (LSGs) from primary Sjögren's syndrome (SS) patients by examining the selective localization of T helper (Th) subsets such as Th1, Th2, Th17 regulatory T cells (Tregs) and follicular T helper cells (Tfh). The expression of cytokines and transcription factors associated with these Th subsets in the LSGs from 54 SS patients and 16 healthy controls was examined using real-time poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 51 publications
5
72
0
1
Order By: Relevance
“…High IL10 expression levels were found in pSS patients in our study. Previous works showed high IL10 mRNA expression in salivary glands of pSS patients [49][50][51][52]. Furthermore, Fox et al suggested that salivary gland CD4+ T cells produce over 40-fold more IL10 mRNA than peripheral blood CD4+ T cells from the same patient or normal controls, moreover, increased levels of IL-10 were found in saliva of pSS patients suggesting that the elevated mRNA levels detected in their glandular tissue correlated with local protein synthesis [49].…”
Section: Discussionmentioning
confidence: 94%
“…High IL10 expression levels were found in pSS patients in our study. Previous works showed high IL10 mRNA expression in salivary glands of pSS patients [49][50][51][52]. Furthermore, Fox et al suggested that salivary gland CD4+ T cells produce over 40-fold more IL10 mRNA than peripheral blood CD4+ T cells from the same patient or normal controls, moreover, increased levels of IL-10 were found in saliva of pSS patients suggesting that the elevated mRNA levels detected in their glandular tissue correlated with local protein synthesis [49].…”
Section: Discussionmentioning
confidence: 94%
“…Patients with higher Tfh cell proportions also had elevated serum levels of IL-12 and IL-21 [6]. Maehara et al have described that the expression of Th2 and certain Tfh-related molecules was associated with robust lymphocytic accumulation and ectopic GC formation [7]. We also investigated the localization of Tfh cells in the lymphocyte infiltration in labial salivary gland (LSG) biopsies gained from pSS patients at the time of disease onset, and found that Tfh cell markers [CD84, PD-1 and B cell lymphoma 6 protein (Bcl-6)] occurred predominantly in more organized lymphoid structures with higher focus scores [8], which indicates that Tfh cells may also be good therapeutic targets in pSS.…”
Section: Cxcr5mentioning
confidence: 99%
“…52 Nonetheless, significant increase in T H 2 cytokines is observed in GC-positive patients. 53 The authors' group previously demonstrated the association between IL-18, a known cytokine involved in the T H 1/T H 2 switch, with the increased production of antibodies against ENA. 54 Another cytokine, IL-21, involved in T H 17 cell homeostasis, plasma cells differentiation, and GC formation, is found in pSS salivary glands.…”
Section: T Lymphocytesmentioning
confidence: 98%